Innovative pedagogies in CDIO implementation in engineering education / Asmidar Alias, Nur Asmaliza Mohd Noor and Noraida Mohd Saim - Alias, Asmidar; Mohd Noor, Nur Asmaliza; Mohd Saim, Noraida (UiTM Press, 2020)
Engineering accreditation council (EAC) and Engineering Technology Accreditation Council (ETAC) requires CDIO initiative to be implemented in engineering programs. In term of delivery, CDIO standards emphasis on integrated learning experiences and active learning. While there formed curriculum has been developed at macro level, changes impact directly on academics' skills development and delivery to suit 21st century learning environment which are ubiquitous, flexible and technology based. Faculty of Civil Engineering UiTM Pahang (FCE) shared the classroom implementation applying innovative pedagogies to provide students with learning experiences stresses engineering fundamentals that are set in the context of Conceiving - Designing - Implementing - Operating (CDIO). The paper describes the diversity of classroom practices shared by FCE, progress and impact.